A Covalent Cysteine‐Targeting Kinase Inhibitor of Ire1 Permits Allosteric Control of Endoribonuclease Activity. (7th March 2016) - Waller, Daniel D.; Jansen, Gregor; Golizeh, Makan; Martel‐Lorion, Chloe; Dejgaard, Kurt; Shiao, Tze Chieh; Mancuso, John; Tsantrizos, Youla S.; Roy, René; Sebag, Michael; Sleno, Lekha; Thomas, David Y.
Abstract: The unfolded protein response (UPR) initiated by the transmembrane kinase/ribonuclease Ire1 has been implicated in a variety of diseases. Ire1, with its unique position in the UPR, is an ideal target for the development of therapies; however, the identification of specific kinase inhibitors is challenging. Recently, the development of covalent inhibitors has gained great momentum because of the irreversible deactivation of the target. We identified and determined the mechanism of action of the Ire1‐inhibitory compound UPRM8. MS analysis revealed that UPRM8 inhibition occurs by covalent adduct formation at a conserved cysteine at the regulatory DFG+2 position in the Ire1 kinase activation loop. Mutational analysis of the target cysteine residue identified both UPRM8‐resistant and catalytically inactive Ire1 mutants. We describe a novel covalent inhibition mechanism of UPRM8, which can serve as a lead for the rational design and optimization of inhibitors of human Ire1. Abstract : Dual‐action inhibitor : We demonstrate covalent inhibition of the dual enzymatic activities of Ire1 by the pyrimidinedione UPRM8. UPRM8 acts as a type IV kinase inhibitor by modifying the DFG+2 cysteine in the kinase activation loop, thereby resulting in allosteric inhibition of Ire1 ribonuclease.